A novel approach to treating osteoarthrosis as a chronic inflammatory disease - Rimma Mikhailovna Balabanova (Современная ревматология, 2013)
A large role in the pathogenesis of osteoarthrosis (OA) is assigned to proinflammatory cytokines, such as interleukin 1 (IL1) and tumor necrosis factor-α, which activate catabolic processes in the cartilaginous tissue and subchondral bone. Diacerein is a medication that is able to block IL1 receptors, to lower the activity of metalloproteinases and nitric oxide, and thus to prevent joint inflammation and destruction in OA.